2016
DOI: 10.3390/pathogens6010001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter jejuni in Lizard Faeces from Central Australia Using Quantitative PCR

Abstract: Worldwide, Campylobacter is a significant cause of gastrointestinal illness. It is predominately considered a foodborne pathogen, with human exposure via non-food transmission routes generally overlooked. Current literature has been exploring environmental reservoirs of campylobacteriosis including potential wildlife reservoirs. Given the close proximity between lizards and human habitats in Central Australia, this study examined the presence of Campylobacter jejuni from lizard faeces collected from this regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…[ 39 ]. The common lizard hosts identified included bearded dragons ( Pogona vitticeps ) [ 34 , 40 ], western beaked gecko (Rhynchoedura odura) [ 34 ], Hydrosaurus pustulatus [ 41 ], green iguana (Iguana iguana ) [ 42 ], Pogona henrilawsonii, Sauromalus ater, Hemitheconyx caudicinctus [ 43 ] and blotched blue-tongued skink (Tiliqua nigrolutea) [ 44 , 45 ]. Five snake species were also identified namely; Heterodon nasicus , Orthriophis taeniurus, Boa constrictor, Python reticulatus [ 45 ] and Morelia amethistina [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 39 ]. The common lizard hosts identified included bearded dragons ( Pogona vitticeps ) [ 34 , 40 ], western beaked gecko (Rhynchoedura odura) [ 34 ], Hydrosaurus pustulatus [ 41 ], green iguana (Iguana iguana ) [ 42 ], Pogona henrilawsonii, Sauromalus ater, Hemitheconyx caudicinctus [ 43 ] and blotched blue-tongued skink (Tiliqua nigrolutea) [ 44 , 45 ]. Five snake species were also identified namely; Heterodon nasicus , Orthriophis taeniurus, Boa constrictor, Python reticulatus [ 45 ] and Morelia amethistina [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…With human–wildlife interactions becoming more common, the likelihood of zoonotic spread of campylobacteriosis is increasing [ 28 , 32 , 33 ]. However, information about horizontal transmission of Campylobacter through non-foodborne routes is limited, and the zoonotic nature of the disease is often overlooked [ 32 , 34 ]. One potentially overlooked host is squamates [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported for Australian rangeland goats. Molecular methods including qPCR offer some advantages for enumeration and detection of Salmonella and Campylobacter in faeces and food, including greater specificity, sensitivity and reproducibility than conventional diagnostic methods (Maciel et al, 2011;Singh et al, 2011;Zhang et al, 2011;Whiley et al, 2016). The present study demonstrated rapid detection of S. enterica and Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter in faeces and food can offer some advantages over culture, including speed, and greater specificity, sensitivity and reproducibility (Maciel et al, 2011;Singh et al, 2011;Zhang et al, 2011;Whiley et al, 2016). Molecular tools based on qPCR have been used to characterise faecal carriage of S. enterica and Campylobacter spp.…”
Section: Molecular Methods Including Quantitative Pcr (Qpcr) For Detementioning
confidence: 99%